Alliance Quebec Youth Seek Meeting with Premier - Alliance Quebec (AQ) (1999)

Transfer of Manpower Could Sacrifice Essential Protections for Minority-Language Services and Information : AQ - Alliance Quebec (AQ) (1997)

Alliance Quebec Brief to the Standing Committee on Cultural Communities & Immigration on the Charter of the French Language - Alliance Quebec (AQ) (1983)
More than a year and a half dgo, the Premier of this province publically called for a dialogue on Bill 101. He stated the hope that the dialogue would be fruitful, and that it would be marked by reasonableness and good faith on the part of everyone concerned. Alliance Quebec, which from the beginning of its existence has proven its commitment to reasonab'l eness and good faith, remains convinced that Quebecers can attain a fair, meaningful and pr oductive resolution of the language debate. This is a debate which has continued for too long, consuming or diverting energy, provoking friction and causing in human terms, considerable damage and loss. We can Iive together, French-speaking and Enlish-speaking Quebecers, in dignity, security and mutual respect; the obstacles are not insurmountable and it is time that they were removed.

A Policy for the English-speaking Community of Quebec - Alliance Quebec (AQ) (1982)
We are almost one million English-speaking Quebecers. We regard Quebec as our home. Our community has participated in more than two hundred years of Quebec's history. We have contributed to the building of one of the world's most stable, prosperous and culturally rich societies. We believe that the interplay of the influences of Quebec's French-speaking and English-speaking peoples has been mutually enriching.